The governance of natural resources in Zimbabwe: the case study of the Marange diamonds - Taruvinga, Gwinyai Regis (My University, 2016)
The governance of natural resources plays an important role in the distribution of resources in any state. The failure of a government to effectively administer natural resources will result in a country failing to benefit from the resources economically. This research paper explores how from 2006 to 2013 the Zimbabwean government handled the discovery of diamonds in the Marange area which is situated just outside Zimbabwe’s third largest city, Mutare. Zimbabwe has had a tumultuous millennium which has seen farm invasions, controversial elections and a crippled economy. The discovery of the diamonds was expected to aid the country’s faltering economy, but instead the diamonds only benefitted a close knit group of individuals who were aligned to the ruling party, ZANU PF. The ruling party in Zimbabwe has enjoyed a stranglehold on the Zimbabwean political landscape and the discovery of the Marange diamonds solidified this stranglehold. The diamonds helped ZANU PF revive its waning political fortunes after the party had joined a coalition government with MDC T after the controversial elections in 2008. The diamonds in Marange are an example of how ZANU PF has been able to use the country’s resources to prop up its waning influence on the Zimbabwean political landscape. The discovery of the diamonds in Zimbabwe mirrors other African countries where rather than being a blessing to local communities natural resources become a curse.
A dissertation presented in partial fulfilment of the requirement of the Master of Arts in Political Studies, Faculty of Humanities at the University of the Witwatersrand, Johannesburg, 2016
Keywords: Diamond mines and mining--Government policy--Zimbabwe; Zimbabwe--Politics and government; Zimbabwe--Economic conditions